POLA PEMBERIAN MAKAN DENGAN STATUS GIZI PADA ANAK USIA PRASEKOLAH (3 - 5 TAHUN) (Di TK Dharma Wanita 1 Desa Bungur Kecamatan Sukomoro Kabupaten Nganjuk) - Rahayu Budi Utami (JURNAL SABHANGA, 2023)
Preschool age is a time of vulnerability to nutritional problems and vitamin deficiencies. Child feeding patterns are very important for the survival and development of a child. This study aims todetermine the relationship between feeding patterns and the nutritional status of preschool children(3 - 5 years) (at Dharma Wanita 1 Kindergarten, Bungur Village, Sukomoro District, NganjukRegency).